The Eruca sativa Genome and Transcriptome: A Targeted Analysis of Sulfur Metabolism and Glucosinolate Biosynthesis Pre and Postharvest - Bell, Luke; Chadwick, Martin; Puranik, Manik; Tudor, Richard; Methven, Lisa; Kennedy, Sue; Wagstaff, Carol (Frontiers in Plant Science, 2020)
Rocket (Eruca sativa) is a source of health-related metabolites called glucosinolates (GSLs) and isothiocyanates (ITCs) but little is known of the genetic and transcriptomic mechanisms responsible for regulating pre and postharvest accumulations. We present the first de novo reference genome assembly and annotation, with ontogenic and postharvest transcriptome data relating to sulfur assimilation, transport, and utilization. Diverse gene expression patterns related to sulfur metabolism, GSL biosynthesis, and glutathione biosynthesis are present between inbred lines of rocket. A clear pattern of differential expression determines GSL abundance and the formation of hydrolysis products. One breeding line sustained GSL accumulation and hydrolysis product formation throughout storage. Multiple copies of MYB28, SLIM1, SDI1 and ESM1 have increased and differential expression postharvest, and are associated with GSLs and hydrolysis product formation. Two glucosinolate transporter gene (GTR2) copies were found to be associated with increased GSL accumulations in leaves. Monosaccharides (which are essential for primary metabolism and GSL biosynthesis, and contribute to the taste of rocket) were also quantified in leaves, with glucose concentrations significantly correlated with the expression of numerous GSL-related genes. Significant negative correlations were observed between the expression of glutathione synthetase (GSH) genes and those involved in GSL metabolism. Breeding line ‘B’ showed increased GSH gene expression and low GSL content compared to two other lines where the opposite was observed. Co-expression analysis revealed senescence (SEN1) and oxidative stress-related (OXS3) genes have higher expression in line B, suggesting that postharvest deterioration is associated with low GSL concentrations.